PENINGKATAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE PEMBELAJARAN KOOPERATIF MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) - Suhari Suhari (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
The purpose of this research is (1) to describe the improvement of Mathematics learning achievement after the implementation of cooperative learning, (2) to describe the influence of learning motivation after applying cooperative learning, (3) to give an accurate learning method in improving student achievement and make students active in teaching and learning activities. This research uses action research for three rounds. each round consists of four stages: design, activity and observation, reflection, and revision. From the analysis result, it is found that the students' learning achievement has improved from cycle I to cycle III, that is cycle I (68,42%), cycle II (81,58%), cycle III (94,74%). The conclusion of this research is cooperative learning method can have a positive effect on student achievement and motivation of IX class SMP Negeri 1 Paciran.